Acceptance of Online Health Services for Self-Help in the Context of Mental Health: Understanding Young Adults' Experiences. Issue 2 (3rd July 2018) - Taiminen, Heini; Saraniemi, Saila
ABSTRACT: This article explores the understanding of the acceptance of online health services from a self-help perspective in the context of mental health. By examining the experiences of young adults, this article develops a framework to leverage the current understanding of the factors that would support the acceptance and use of these types of services. To this end, a multidisciplinary perspective incorporating knowledge from the service marketing, health, and information systems literature is used. The results suggest that the production of online services that are meant for self-help purposes necessitates a focus on the acceptance of technology and, more importantly, instrumental value creation, as the purpose of using these types of services should be better understood and supported by technological solutions. This study also identifies several technological features supporting both the acceptance of technology and users' ability to achieve well-being. Furthermore, when developing services for health self-help purposes, the issue of branding to increase acceptance should be assessed. From a user perspective, there appears to be a difference regarding whether the services are positioned as health services or as wellness services.